Approaches to Stem Education around the World, What We can Learn from Them - Golegou, Eirini; Peppas, Kostas (NPRC Journal of Multidisciplinary Research, 2025)
The article commences with a historical review of STEM education, followed by a discussion of its implementation across various nations worldwide. The objective of the research is to identify and categorize the diverse approaches to implementing STEM education, with a view to establishing standards that can serve as a model for its introduction in other countries. The primary conclusion of the research is that while STEM education can be incorporated into a nation's educational system, it does not necessitate the entire curriculum being based on it.